2021
DOI: 10.3390/healthcare9091193
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Taiwanese Version of the Tilburg Frailty Indicator for Community-Dwelling Older Adults

Abstract: Screening the frailty level of older adults is essential to avoid morbidity, prevent falls and disability, and maintain quality of life. The Tilburg Frailty Indicator (TFI) is a self-report instrument developed to assess frailty for community-dwelling older adults. The aim of this study was to explore the psychometric properties of the Taiwanese version of TFI (TFI-T). The sample consisted of 210 elderly participants living in the community. The scale was implemented to conduct a confirmatory factor analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The three-factor model showed better fit, but items 2, 5, and 6 showed loadings < 0.40 with the physical domain, as previously showed by other authors [13,18,21]. Moreover, previous studies also found low factor loadings for items 13, 15 (social domain) [13,18], and 14 (social domain) [18,21]. It must be considered that low factor loadings indicate that the item (indicator) does not relate to the rest of indicators in the factor or dimension, and therefore cannot be aggregated to them.…”
Section: Discussionsupporting
confidence: 83%
“…The three-factor model showed better fit, but items 2, 5, and 6 showed loadings < 0.40 with the physical domain, as previously showed by other authors [13,18,21]. Moreover, previous studies also found low factor loadings for items 13, 15 (social domain) [13,18], and 14 (social domain) [18,21]. It must be considered that low factor loadings indicate that the item (indicator) does not relate to the rest of indicators in the factor or dimension, and therefore cannot be aggregated to them.…”
Section: Discussionsupporting
confidence: 83%
“…The mean TFI-T score was 5.69 (SD = 3.22). A cutoff score of ≥5.5 was used to diagnose frailty [ 27 ]. Accordingly, the conditions of the older adults in this study can be divided into two groups: frail (TFI-T ≥ 5.5, n = 109, 51.9%) and robust (TFI-T < 5.5, n = 101, 48.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Frailty was measured by the Taiwanese version of the Tilburg Frailty Indicator (TFI-T) [ 27 ]. The scale is a widely used frailty screening scale with good reliability and validity [ 27 ] that consists of 15 questions, resulting in a total frailty score ranging from 0 to 15. A higher total score indicates a worse degree of frailty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the TFI for assessing frailty fits well with nursing because this questionnaire is used to assess the total functioning of an older person. Many studies that were conducted in different countries have shown that the TFI is a valid and reliable instrument to assess frailty in community-dwelling older people, such as in the Netherlands ( Gobbens et al, 2010b ), Poland ( Uchmanowicz et al, 2014 ), Brazil ( Santiago et al, 2013 ), China ( Dong et al, 2017 ), Iran ( Mazoochi et al, 2020 ), and Taiwan ( Lin et al, 2021 ).…”
Section: Discussion Of Topicmentioning
confidence: 99%